Emerging of HIV drug resistance: Epidemiology, diagnosis, treatment and prevention - Sasisopin Kiertiburanakul (2018)
Antiretroviral therapy for HIV/AIDS patients are used globally including in resource-limited settings. Successful outcomes are not always observed and HIV resistance to antiretroviral agents is a major cause of treatment failure. Both primary and secondary drug resistance have been described and reported worldwide. Primary resistance, which presumably means that individuals are infected with drug-resistant virus and secondary resistance typically, means a result of treatment failure. Pathogenesis of resistance of each antiretroviral drugs class differs and depends on the mechanism of action of the drugs. Three main laboratory investigations for diagnosis of treatment failure and HIV drug resistance are HIV RNA level, CD4 cell count, and HIV resistance testing. Management concepts for patients with HIV drug resistance are discussed. Strategies for prevention of HIV resistance emergence include finding cases with acute HIV infection, early detection of virological failure, and behavioral interventions such as adherence and condom usage. © 2009 Bentham Science Publishers Ltd.